2019
DOI: 10.1159/000496499
|View full text |Cite
|
Sign up to set email alerts
|

Mentalization as Mediator between Adult Attachment and Interpersonal Distress

Abstract: Background: The aim of this study was to investigate the mediating role of mentalization in the association between adult attachment and interpersonal problems. Methods: The sample consisted of 89 patients with different types of mental disorders who were at the beginning of treatment in one of two medical centers. Both mediational analysis and path analysis were used to test the model. Results: The proposed model revealed a good model fit. The data indicate that mentalization fully mediates the effect of atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 54 publications
3
26
1
Order By: Relevance
“…A direct effect of childhood trauma on mentalizing was also identified in the current study. The result is in line with previous findings [13,[16][17][18][19][20] indicating that early trauma may weaken mentalizing abilities. Individuals with poorer mentalizing may perceive the mental states of others as threatening [15].…”
Section: Discussion/conclusionsupporting
confidence: 92%
See 2 more Smart Citations
“…A direct effect of childhood trauma on mentalizing was also identified in the current study. The result is in line with previous findings [13,[16][17][18][19][20] indicating that early trauma may weaken mentalizing abilities. Individuals with poorer mentalizing may perceive the mental states of others as threatening [15].…”
Section: Discussion/conclusionsupporting
confidence: 92%
“…The current study further examined the relationship between attachment and mentalizing and found it to be bidirectional. Although previous studies found that attachment insecurity contributed to mentalizing [16,19], Fonagy and Bateman [41] pointed out that it would be appropriate to describe attachment and mentalizing as interrelated phenomena from different starting points in adulthood. They suggested that attachment and mentalizing may interact in a complex causal way, in which early experiences of maltreatment lead to disruptions of the attachment system, which in turn causes mentalizing failure when the attachment system is activated.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mentalizing describes the human ability to comprehend one's own and others' mental states and is seen as one of the core competencies of psychotherapists; the concept overlaps with the concepts of empathy [1,2]. Empathic abilities based on mentalization skills are a therapy factor with a known clinically relevant effect size on therapy outcome [3][4][5][6][7][8]. Mentalization based interventions have been shown to be important in the treatment of several mental disorders, including borderline personality disorder and other personality disorders [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Empathic abilities based on mentalization skills are a therapy factor with a known clinically relevant effect size on therapy outcome [3][4][5][6][7][8]. Mentalization based interventions have been shown to be important in the treatment of several mental disorders, including borderline personality disorder and other personality disorders [4][5][6][7][8]. Impairments in mentalization are associated with pathology of the self and with insecure attachment [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%